Impact of cover crops and soil drainage in CH4 and N2O emissions under irrigated rice cultivation - Zschornack, Tiago; da Rosa, Carla Machado; Camargo, Estefânia Silva; dos Reis, Cecília Estima Sacramento; Schoenfeld, Rodrigo; Bayer, Cimélio (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of the winter cover crops ryegrass (Lolium multiflorum) and ryegrass+birdsfoot trefoil (Lotus corniculatus), as well as of partial soil drainage, on CH4 and N2O emissions in an Alfisol cultivated with paddy rice. Air samples were collected weekly using static closed chambers partially inserted in the soil (0.05 m). Partial global warming potential (pGWP= CH4×25+N2O×298) and yield-scaled pGWP were calculated. Partial soil drainage was established with temporal suspensions of the irrigations for periods of 8 to 15 days, during three occasions throughout the crop cycle. Biomass input by cover crop residues increased CH4 fluxes, which exceeded ten times the accumulated emissions of fallow soil. N2O emissions were higher in the ryegrass+birdsfoot trefoil treatment, compared with ryegrass and fallow. Cover crops increased yield-scaled pGWP (0.35 kg CO2eq per kilogram of rice) compared with fallow (0.06 kg kg-1). In the treatments with winter crops, mitigation strategies should focus mainly on CH4, which was responsible for the greater portion (80%) of pGWP. Partial drainage reduced pGWP up to 50% and has great potential for mitigating gas emissions in subtropical irrigated rice production systems.